Operasional Bank Sampah dalam Pembentukan Gaya Hidup Berkelanjutan - Akhmad Luqman Hakim; Dian Hidayati (Jurnal Syntax Admiration, 2023)
The waste bank is one of the important solutions in overcoming the waste problem and forming a sustainable lifestyle. In the waste bank system, waste is collected, processed and recycled to create products of economic value. This abstract discusses the results and discussion of waste bank operations in the context of establishing a sustainable lifestyle. The operational results of the waste bank include reducing waste in landfills (TPA), increasing recycling, creating valuable products, and environmental education. By managing waste efficiently, waste banks reduce negative impacts on the environment and help reduce the use of natural resources. In addition, waste banks also play an important role in shaping a sustainable lifestyle through several discussions. First, the waste bank increases environmental awareness among the public, changes the mindset towards waste, and inspires changes in behavior towards a cleaner and more sustainable environment. Second, active community participation in the waste bank strengthens community involvement in waste management and creates a participatory climate in environmental decision-making. Third, the waste bank opens local economic opportunities by creating products from waste, helping to empower the local community's economy, and reducing social inequality. Furthermore, the waste bank reduces the use of new natural resources by processing used goods into useful products, helping to reduce pressure on the environment. Finally, the operation of the waste bank makes the public aware of the problem of waste and the importance of collective action in dealing with this problem. Overall, waste banks play an important role in shaping sustainable lifestyles by creating positive outcomes and driving behavior change and environmental awareness. The waste bank is an important first step in changing the perspective of waste and forming a more environmentally responsible society.